The Development of Teacher Professional Ethics in the Digital Age from an Islamic Perspective - Wagiman Manik (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2025)
The rapid advancement of digital technology has transformed educational ecosystems, presenting new ethical challenges for teachers such as data privacy, virtual communication, and digital plagiarism—issues inadequately addressed by classical Islamic ethics frameworks. This study aims to formulate an operational and responsive model of teacher professional ethics in the digital era grounded in Islamic values. Employing a qualitative library research approach, data were gathered through thematic content analysis of the Qur'an, hadith, classical scholarly works, and contemporary journals. The findings yield a comprehensive model integrating the principles of amanah (trustworthiness), uswah (role modeling), tabayyun (verification), rahmah (compassion), and sidq (truthfulness) across four dimensions: personal character, ethical digital interactions, secure data management, and academic justice. In conclusion, this model fills gaps in fragmented prior studies by providing a holistic Islamic-based framework. Its primary contributions include practical guidelines for teachers, policy recommendations for schools, and enrichment of contemporary Islamic educational ethics discourse.